2015
DOI: 10.29173/cmplct23335
|View full text |Cite
|
Sign up to set email alerts
|

When Time Makes a Difference: Addressing Ergodicity and Complexity in Education

Abstract: The detection of complexity in behavioral outcomes often requires an estimation of their variability over a prolonged time spectrum to assess processes of stability and transformation. Conventional scholarship typically relies on snapshots to analyze those outcomes, assuming that group means and their associated standard deviations, computed across individuals, are sufficient to characterize the educational outcomes that inform policy, and that time does not matter in this context. In its statistically abstrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 16 publications
1
13
0
Order By: Relevance
“…The research reported here is part of a program of ongoing study of the long range patterns of daily attendance in New York City high schools, and the identification of signs of complex adaptive behavior (fractality, meta-stability) in those patterns. Previous findings were reported by Koopmans (2015a;2015b;2016;2017a;2017b;2018).…”
Section: Exploring the Effects Of Creating Small High Schools On Dailsupporting
confidence: 54%
“…The research reported here is part of a program of ongoing study of the long range patterns of daily attendance in New York City high schools, and the identification of signs of complex adaptive behavior (fractality, meta-stability) in those patterns. Previous findings were reported by Koopmans (2015a;2015b;2016;2017a;2017b;2018).…”
Section: Exploring the Effects Of Creating Small High Schools On Dailsupporting
confidence: 54%
“…CDS argues that both need to be considered in conjunction in order to understand systemic stability and change. The methodological predisposition that follows from these insights is that many repeated observations of the behavior of a system are needed to understand its causal underpinnings (Koopmans, 2015).…”
Section: Conditionality and Irreducibility In Interactionmentioning
confidence: 99%
“…Based on examples from various disciplines, Nicolis and Prigogine seek to find the commonalities between systems, and while their emphasis is on chemistry, physics and biology, their ability to demonstrate of the applicability of transformative models that are specific in the abstract across different fields of knowledge is what makes their search of particular interest. The extension of such change models to education can be readily appreciated by the fact many have already been investigated empirically, such as hysteresis (Stamovlasis, 2006;Stamovlasis & Tsaparlis, 2012), non-periodic attractors (Koopmans, 2015), emergence (Hussain et al 2014) and self-organization and fractality (Fromberg, 2010(Fromberg, , 2016. A discussion of complexity in terms of its transformative capabilities can also be found in Davis and Sumara (2006), who distinguish the construct defined in this way from complicity, i.e., systemic novelty due to repeated interactions, and simplexity, the emergence of simple linear features in complex systems (Stewart, 2007).…”
Section: Performing Transitions Between Statesmentioning
confidence: 99%
See 1 more Smart Citation
“…According to large swathes of empirical and theoretical work, this assumption is invalid for most measurable variables of psychological processes occurring within and between individuals (see, e.g. Molenaar, 2004; Kelderman and Molenaar, 2007; Molenaar and Campbell, 2009; Hamaker, 2012; Koopmans, 2015; Beltz et al, 2016; Hamaker and Wichers, 2017; Fisher et al, 2018). In fact, group statistics rarely represent individual cases and processes (a misconception also referred to as the ecological fallacy).…”
Section: Introductionmentioning
confidence: 99%